RINGs of good and evil: RING finger ubiquitin ligases at the crossroads of tumour suppression and oncogenesis - Lipkowitz, Stanley (2011)
The ubiquitin-proteasome system has numerous crucial roles in physiology and pathophysiology. Fundamental to the specificity of this system are ubiquitin-protein ligases (E3s). Of these, the majority are RING finger and RING finger-related E3s. Many RING finger E3s have roles in processes that are central to the maintenance of genomic integrity and cellular homeostasis, such as the anaphase promoting complex/cyclosome (APC/C), the SKP1–cullin 1–F-box protein (SCF) E3s, MDM2, BRCA1, Fanconi anaemia proteins, CBL proteins, von Hippel–Lindau tumour suppressor (VHL) and SIAH proteins. As a result, many RING finger E3s are implicated in either the suppression or the progression of cancer. This Review summarizes current knowledge in this area.